1959
DOI: 10.1063/1.1777004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Annealing in Perminvar. I. Structural Origin

Abstract: This paper deals with the results of an electron diffraction investigation of the structure of soft magnetic materials which exhibit magnetic annealing. The property of heat treatment in a magnetic field has been found to depend upon the oxygen content present as an impurity and is associated with distinct diffraction phenomena. A structural model based on an interpretation of diffraction results, magnetic properties, and oxygen content is presented. The pertinent conclusions from this study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…It is believed to be related to the fact that they suppress long-range ordering and so may favour local ordering in the field direction. This new mechanism, which we have found to operate in cobaltrich amorphous oxides, appears to be similar to that identified by Heidenreich et al (1959) to be responsible for field annealing in crystalline Co-Ni-Fe (Permendur and Permalloy) alloys and field-induced ordering in Ni3Fe by Nesbitt et al (1965).…”
Section: Relationship Between N~icrostructure and Field-induced Anisosupporting
confidence: 85%
“…It is believed to be related to the fact that they suppress long-range ordering and so may favour local ordering in the field direction. This new mechanism, which we have found to operate in cobaltrich amorphous oxides, appears to be similar to that identified by Heidenreich et al (1959) to be responsible for field annealing in crystalline Co-Ni-Fe (Permendur and Permalloy) alloys and field-induced ordering in Ni3Fe by Nesbitt et al (1965).…”
Section: Relationship Between N~icrostructure and Field-induced Anisosupporting
confidence: 85%
“…From the hysteresis loop of barium ferrite and polyaniline nanocomposites, it has been observed that the material possesses high retentivity (Mr) and coercive force (Hc). The observed hysteresis loop shows little variation from the regular magnetization curve of barium ferrite which may be attributed to annealing conditions and also to the increase in the iron concentration [124]. This type of behavior is observed in ferrites having high Curie temperature and to the slow cooling of the sample which causes slight oxidation of the sample.…”
Section: Magnetic Studiesmentioning
confidence: 74%
“…1 Results for P e r m a l l o y a r e of the g r e a t e s t interest, p a r t i c u l a r l y since o x i d e s a r e t h o u g h t to p l a y a role in the origin of anisotropy in magnetic films (8). 1 Results for P e r m a l l o y a r e of the g r e a t e s t interest, p a r t i c u l a r l y since o x i d e s a r e t h o u g h t to p l a y a role in the origin of anisotropy in magnetic films (8).…”
Section: Discussionmentioning
confidence: 99%